The foreign investment and using modern communication technologies in the disputes resolution - Dine Al Amine, Khayr Al (Opción, 2019)
The paper aims to investigate the foreign investment and using modern communication technologies in the disputes resolution via qualitative comparative analysis. As a result, the Investment Law in force allows the Investment Commission to use electronic means of communication to simplify procedures between the commission and investors. In conclusion, we suggest adding the organization of electronic notification to traditional notification methods in order to keep pace with technological developments and use modern means of communication.